Design and investigation of 1D photonic crystal based structures for BIPV cell colorization by sol-gel dipping technology. (15th January 2023) - Rudzikas, Matas; Donėlienė, Jolanta; Bužavaitė-Vertelienė, Ernesta; Balevičius, Zigmas; Leuvrey, Cedric; Šetkus, Arūnas
Highlights: Optimized 1D photonic crystal structure was proven to be efficient and sufficient for BIPV. 5x5 cm samples were produced with sol–gel dipping technique with annealing at 110 °C. Created structures had 2–3 higher CIE brightness compared to the commercial panels. Tolerable deviations are +/- 0.05 for refractive index and +/- 2% for thickness. Abstract: The growth of the building integrated photovoltaic (BIPV) sector is limited by the apparent lack of ways to create the visual impact of the building at acceptable cost efficiency rates in the current PV market. Thus, in this research digital simulations were combined with experimental studies to design and optimize novel 1D photonic crystal structures acceptable to expand and improve the color palette of PV panels. It was proved that the 3-layered system with TiO2 /SiO2 /TiO2 was both efficient and sufficient for this purpose. Advanced light filtering was implemented experimentally on 5x5 size glass plates with a potentially cheap and simple sol–gel dipping technique with annealing only at 110 °C. The applicability of the proposed technology was validated by manufacturing the PV mini panels that showed 2–3 higher brightness in CIE color space compared to the panels made using commercial solar cells. Experimentally obtained efficiencies were: 18.75% (REF, black), 17.28% (light blue), 17.13% (greenish), 16.52% (yellowish), which is in the range to the commercial colored cells, but could be higher if better cells were used. The technology reliability and scalability were evaluated from analysis of the sensitivity of the 1D photonic crystal parameters to the optical properties of the colored device. The tolerable deviations from the color related numbers are approximately +/- 0.05 for the refractive index spectrum and less than approximately +/- 2% for the thickness. Therefore, the proposed coloring method should be a perspective solution for BIPV, but careful attention should be taken for the technological process optimization.